Educação ambiental e cidadania: a importância da educação ambiental enquanto tema transversal na Escola João Silveira Guimarães - Félix, Renata Soares (2024)
The study analyzes the importance of Environmental Education as a transversal theme in promoting citizenship among students, focusing on the João Silveira Guimarães School in São Bento-PB, Brazil. The research combined a literature review with questionnaires to assess perceptions and practices related to this topic. The results show that, although students recognize the importance of Environmental Education, the content is often approached in a theoretical and superficial way, with limited practical applications. Most students see Environmental Education as an awareness-raising tool, but their responses indicate a narrow understanding influenced mainly by external sources, such as the internet. The analysis highlights that the lack of specific training for teachers and insufficient resources make an interdisciplinary approach difficult and limit the implementation of practical activities. The absence of concrete projects, such as school gardens and recycling programs, was noted as a significant barrier to students' internalization of environmental problems. The study concludes that, to promote critical and engaged citizenship, there is a need for investment in teacher training and improving school infrastructure. The effective integration of Environmental Education as a transversal theme can help to cultivate students who are environmentally aware and capable of applying their knowledge in sustainable actions. This approach would allow students to serve as multipliers of environmental practices within their communities, reinforcing the broader educational goal of sustainability.